PENGEMBANGAN KONSEP PENDIDIKAN ISLAM PADA SURAT LUQMAN AYAT 12-19 BERDASARKAN TAFSIR AL-AZHAR KARYA HAMKA - Mursalin, Hisan; Azkiyannada, Azkiyannada; Hidayat, Tatang (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2023)
Islamic education to date has been poorly applied in social life. Various deviant behaviors of teenagers are rampant in various places. This is closely related to the system built by an Islamic family to educate family members in accordance with the guidance of Islamic teachings. Children's education in Islam aims to instill Islamic values to children in order to make servants of Allah who obey Him and His messenger. This study aims to explore the educational values contained in the Quran sourced from Al-Azhar commentary and insights that are considered relevant and useful to discuss. This study uses qualitative methodology which is a library research. The Quran is used as the primary source and the interpretation concluded by Hamka in surah Luqman with the support of secondary sources in the form of books, articles, journals, and all other supporting information. It can be concluded that there are three basics that must be a benchmark in life according to Hamka, especially for education, namely: First, Aqidah, is the basis of children's faith in the Godhead. Second, Worship, the vertical relationship of children as a manifestation of the implementation of aqidah. Third, Akhlak, children's education in behavior towards parents, society and the environment.